Nonlinear adaptive control with integrated performances for waverider. (28th March 2019) - Yang, Liuqing; Liu, Yanbin; Zhang, Yong
This article provides a nonlinear controller for waveriders with input saturation to improve transient performances. First, the exact linearization is applied to change an affine nonlinear model to a linear time-invariant model for waveriders. Then, the linear and nonlinear feedback control law is applied for the obtained linearized model for waveriders, and system stability of the presented control law is proved accordingly. Furthermore, the system robustness and improving transient performances are discussed for waveriders. Finally, an example is given for a longitudinal model of the waverider, and the results demonstrate that the closed-loop systems can track the anticipated commands, while guaranteeing the expected integrated performances for waveriders.